1999
DOI: 10.1038/sj.onc.1203345
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic mutant of Gα12 stimulates cell proliferation through cycloxygenase-2 signaling pathway

Abstract: Expression of the GTPase-de®cient, activated mutant asubunit of the heterotrimeric G protein G12 (Ga 12 QL) leads to the neoplastic transformation of ®broblast cell lines. The mitogenic pathway regulated by Ga 12 QL includes an extensive signaling network involving several small GTPases and various kinases. In addition, Ga 12 QL has been shown to potentiate the serum-induced phospholipase-A 2 activity in NIH3T3 cells. In the present study, we demonstrate that cycloxygenase-2 (COX-2) pathway is involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Therefore, G 12 and G q play important roles in ET-1-induced AA release. These results are consistent with the previous report, which demonstrated that the GTPase-deficient activated mutant of G 12 stimulates AA release in NIH 3T3 cells (Dermott et al, 1999). ET-1-induced AA release was not inhibited completely by G 12 G228A in this study (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, G 12 and G q play important roles in ET-1-induced AA release. These results are consistent with the previous report, which demonstrated that the GTPase-deficient activated mutant of G 12 stimulates AA release in NIH 3T3 cells (Dermott et al, 1999). ET-1-induced AA release was not inhibited completely by G 12 G228A in this study (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, aspirin acts as nonspecific COX inhibitor; at 10 mM it inhibits COX-1 while at a concentration higher than 100 mM inhibits also COX-2 (Dermott et al, 1999). In our experiments, aspirin at the inhibitory concentrations for COX-1 (2.5 and 5 mg ml À1 ) did not exhibit any effect on HTR-IR cell proliferation.…”
Section: Discussioncontrasting
confidence: 61%
“…In addition, there is substantial evidence that Ga 12/13 proteins mediate signaling pathways involved in cell growth and tumorigenesis (Chan et al, 1993;Jiang et al, 1993;Jones and Gutkind, 1998;Dermott et al, 1999). Whereas Ga 12 proteins have been directly linked to regulatory molecules such as the Rho-directed guanine nucleotide exchange factor p115 Hart et al, 1998) and the GTPase-activating protein RasGAP1 , the signi®cance of these interactions in relation to the developmental and oncogenic roles of Ga 12 proteins has not been clearly de®ned.…”
mentioning
confidence: 99%